High-frequency oscillatory ventilation is an effective treatment for severe pediatric acute respiratory distress syndrome with refractory hypoxemia - Guo YX; Wang ZN; Li YT; Pan L; Yang LF; Hu Y; Sun YY; Cai LM; Chen ZG (Dove Medical Press, 2016)
Yu-Xiong Guo,1,* Zhao-Ni Wang,2,* Ya-Ting Li,2 Li Pan,2 Li-Fen Yang,2 Yan Hu,1 Yue-Yu Sun,1 Liang-Ming Cai,2 Zhuang-Gui Chen2 1Pediatric Intensive Care Unit, Department of Pediatrics, Guangdong General Hospital, Guangdong Academy of Medical Sciences, 2Pediatric Intensive Care Unit, Department of Pediatrics, The Third Affiliated Hospital of Sun Yat-sen University, Guangzhou, People’s Republic of China *These authors contributed equally to this work Background and purpose: Early or primary application of high-frequency oscillatory ventilation (HFOV) has been recently suggested not to offer benefit to patients with acute respiratory distress syndrome (ARDS). However, the rescue effects of HFOV on severe pediatric acute respiratory distress syndrome (PARDS) with hypoxemia refractory to conventional mechanical ventilation (CMV) remain unclear. This study aimed to determine whether severe PARDS children would benefit from HFOV when oxygenation deteriorated on CMV and to identify any potential risk factors related to mortality. Patients and methods: In a retrospective and observational study, 48 children with severe PARDS between January 2009 and July 2015 were divided into two groups: 26 in HFOV group and 22 in CMV group. Data regarding demographic, underlying conditions, arterial blood gases and clinical outcomes were collected and analyzed. Results: The arterial partial pressure of oxygen (PaO2)/fraction of inspiration oxygen (FiO2) ratio and PaO2 improved significantly during HFOV, whereas arterial partial pressure of carbon dioxide (PaCO2) and oxygenation index decreased. There was no statistical difference in the in-hospital mortality between the groups (P=0.367). The odds ratio of survival in HFOV group was 2.74 (95% confidence interval 0.52 to 14.58, P=0.237). The pediatric intensive care unit length of stay and total ventilation duration were longer in HFOV group (P=0.048 and P=0.000, respectively). Vasoactive agents were used more frequently in HFOV group (P=0.007). The incidence of new air leak was similar between the two groups (P=0.674). The presence of multiple organ dysfunction syndrome and heavier body weight were identified as predictors of mortality in the HFOV group (P=0.006 and P=0.020, respectively). Conclusion: HFOV as an efficient alternative therapy could significantly improve hypoxemia and promote CO2 removal in severe PARDS children when oxygenation progressively worsens on CMV. Keywords: pediatric acute respiratory distress syndrome, high-frequency oscillatory ventilation, mechanical ventilation, children